A data-based approach to the qualitative characterization of ore variability, C.S. Macomber, J.E. Gebhardt, W. Lee, and B. Temel Mckenna - C. S. Macomber; J. E. Gebhardt; W. Lee; B. Temel Mckenna (The Southern African Institute of Mining and Metallurgy, 2020)
X-ray diffraction (XRD) data was extracted from various sources to develop qualitative ternary and tetrahedral plots differentiating mineralogy, bond work index (BWi) and hardness of ore bodies at different mine sites. A large number of historic reports and compiled characterization laboratory data were used to create a searchable "data lake." The data lake provides a means to locate, consolidate, and visually represent XRD from disparate sources. Visualizations with large amounts of mineral ore XRD characterization data provide a qualitative assessment of ore properties, including comminution qualities such as material hardness. The visual map can be employed to quickly estimate expected ore character and behavior, given XRD analysis of samples from newly characterized and unfamiliar ore. Keywords: Mineralogy, Characterization, Comminution, Database, Ternary, Tetrahedral